Value Added Analysis and Development Strategy of Canned Traditional Food Vegetable Candle (Saccharum edule) - Rasulu, Hamidin; Wulansari, Angela; Albaar, Nurjanna; Husen, Janiah; Mustafa, Ikrima M.; Suwito; Juharni (Jurnal AGRISEP, 2026)
Vegetable candle (sayur lilin in Indonesia) (Saccharum edule) is a traditional food typical of North Maluku, which is processed from sugarcane flowers and cooked using coconut milk. The application of canning technology acts as an effective preservation method to increase the shelf life of products while ensuring food safety. This research aims to analyze added value and formulate the right development strategy for the canned vegetable candle industry. This study uses SWOT analysis and value-added analysis with the Hayami approach. A study of the data revealed that canned vegetable candles had a 70.57% enhanced value ratio. The internal conditions of the business were in the moderate category, while the external environment showed strong conditions. Based on the IE matrix, the canned vegetable business is in Quadrant II with a growth and building strategy position. Thus, the best options for development are market entry tactics, market development, and product development. The SWOT analysis and added value results also indicate that canned veggies have a lot of room for growth. Recommended strategies include promotion through social media, product socialization, collaboration with relevant stakeholders and local governments, and adaptation of recipes to increase product competitiveness.